Effect of Giving Different Doses of Vitamin E in Feed to the Level of Gonad Maturity of Tilapia (Oreochromis niloticus) - Tarigan, Gunawan; Arthana, I Wayan; Pebriani, Dewa Ayu Angga (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 2 (2021): ATBESDO - 10.24843/ATBES.2021.v05.i02.p05, 2021)
One of the nutrients that can be given to brood feed fish to improve reproductive performance and egg quality is vitamin E. Vitamin E has a very important role in increasing fish reproduction because vitamin E functions as an antioxidant that can maintain the presence of fatty acids and prevent fat oxidation in the fish cell membrane and can accelerate the secretion of reproductive hormones. This study aims to determine the effect of vitamin E in feed at different doses on the level of gonad maturity of tilapia. The research was conducted at the Fisheries Laboratory of the Faculty of Marine and Fisheries, Udayana University from July to August 2020. The samples of fish tested were tilapia ( Oreochromis niloticus ) obtained from the Teratai fishing pond, Sanur Bali. Vitamin E used was Ovagrow Vit E with a vitamin E content of 50%. The CRD method (completely randomized design) was used with four treatments and three replications. The doses of vitamin E that were mixed into the feed were 0, 100, 300, and 500 mg/kg of feed. The results showed that the administration of vitamin E mixed in the feed at different doses had a significant effect on the achievement of gonad maturity level, gonad somatic index (GSI), and Fecundity (P <0.05). Provision of vitamin E at a dose of 300 mg/kg of feed was the best dose for ripening tilapia gonads. The gonad maturity level developed up to maturity stage IV, the GSI value was (3.56 ± 0.46) and the fecundity value was (1379 ± 289).